Essential practical NMR for organic chemistry - 524607 Richards, S. A.; Hollerton, J. C. (John C.), 1959- (Chichester, West Sussex, UK. : John Wiley, 2011)
Introduction -- Getting started -- Preparing the sample -- Spectrum acquisition -- Processing -- Interpreting your spectrum -- Delving deeper -- Further elucidation techniques : part 1 -- Further elucidation techniques : part 2 -- Carbon-13 NMR spectroscopy -- Some of the other tools -- Some of the other nuclei -- Quantification -- Safety -- Software -- Problems -- Glossary